2014
DOI: 10.1002/mds.25826
|View full text |Cite
|
Sign up to set email alerts
|

Morphologic changes of dendritic spines of striatal neurons in the levodopa‐induced dyskinesia model

Abstract: Maladaptive plasticity at corticostriatal synapses plays an important role in the development of levodopa‐induced dyskinesia. Recently, it has been shown that synaptic plasticity is closely linked to morphologic changes of dendritic spines. To evaluate morphologic changes of dendritic spines of two types of striatal medium spiny neurons, which project to the internal segment of globus pallidus or the external segment of globus pallidus, in the levodopa‐induced dyskinesia model, we used 6‐hydroxydopamine‐lesion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

11
91
1

Year Published

2015
2015
2017
2017

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 75 publications
(103 citation statements)
references
References 34 publications
11
91
1
Order By: Relevance
“…Several studies have demonstrated that the dendritic spines of medium spiny neurons (MSNs) in the CPu change their morphology in LID models (Fieblinger et al, 2014;Nishijima et al, 2014;Suarez et al, 2016;Suarez et al, 2014;Zhang et al, 2013). These morphological changes suggest maladaptive MSN excitatory synapses in the CPu.…”
mentioning
confidence: 99%
See 4 more Smart Citations
“…Several studies have demonstrated that the dendritic spines of medium spiny neurons (MSNs) in the CPu change their morphology in LID models (Fieblinger et al, 2014;Nishijima et al, 2014;Suarez et al, 2016;Suarez et al, 2014;Zhang et al, 2013). These morphological changes suggest maladaptive MSN excitatory synapses in the CPu.…”
mentioning
confidence: 99%
“…1B). Beginning 6 weeks after the apomorphine challenge, the 6-OHDA-lesioned and sham-operated rats received 50 mg/kg levodopa methyl ester with 12.5 mg/kg benserazide, a dopa decarboxylase inhibitor (PD-Levodopa group and Control-Levodopa group), or saline (PD-Saline group and ControlSaline group), twice daily for 14 consecutive days (Nishijima et al, 2014) (Fig. 1B).…”
mentioning
confidence: 99%
See 3 more Smart Citations